STRENGTHENING DA’I ROLES IN SOUTH SUMATRA: STRATEGIES OF THE ISLAMIC COMMUNICATION AND BROADCASTING KPI STUDY PROGRAM AND ITS ALUMNI - Syarifudin, Achmad; Muhamad Randicha Hamandia (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2023)
The KPI Study Program at UIN Raden Fatah Palembang faces challenges in preparing graduates to fulfill the role of professional da’i in South Sumatra. Despite being designed to produce skilled da’i with strong academic and Islamic qualifications, the program’s curriculum, planning, and evaluation processes are misaligned with this objective, leading to a lack of graduate readiness. This study, using a qualitative approach with Miles and Huberman's analysis, highlights that while there are significant opportunities for da’i. Due to the increasing number of mosques, mushallas, and da’wah institutions, these opportunities are not being fully utilized. Key obstacles include alumni perceptions that the da’i role does not exclusively require KPI graduates, inadequate public speaking skills, and insufficient grounding in Islamic teachings during the program. To address these issues, the study recommends revising the curriculum to prioritize da’wah-related courses, practical methodologies, and Islamic knowledge, ensuring that KPI graduates are better equipped to take on the responsibilities of da’i, muballigh, and ulama.